EMERGING TRENDS IN MARRIED BY ACCIDENT (MBA) MARRIAGES: THE ROLE OF RELIGIOUS COUNSELING INVOLVEMENT IN KUALUH LEIDONG - Sari, Intan Kumala; Ja'far, Hasbullah (Al-Risalah, 2024)
This research paper investigates the phenomenon of Married By Accident (MBA) marriages in Kualuh Leidong, focusing on the contributing factors and the effectiveness of religious counseling in addressing this issue. The study aims to understand the social, economic, and familial dynamics leading to MBA marriages and the role of religious and community interventions in mitigating these occurrences. Utilizing a qualitative research approach, this study employs interviews with key informants, including religious counselors and local residents, alongside a review of relevant literature and socio-economic data. The data were collected through in-depth interviews and field observations in Kualuh Leidong, analyzed thematically to identify patterns and insights related to MBA marriages. The findings reveal that MBA marriages in Kualuh Leidong are influenced by a combination of internal and external factors. Internal factors include a lack of religious understanding and weak self-control, while external factors involve inadequate parental supervision, economic hardship, and social media's impact. The study also highlights the increasing trend of MBA marriages in 2024, attributed to insufficient religious counseling and the role of socio-economic challenges. This research provides a novel exploration of MBA marriages in a specific regional context, highlighting the intersection of religious, economic, and social factors. It offers new insights into the effectiveness of religious counseling in preventing MBA marriages and the impact of socio-economic conditions on family dynamics. he study underscores the need for enhanced religious education and community support to address the root causes of MBA marriages. It suggests that more comprehensive and culturally sensitive counseling programs are necessary to prevent early marriages and address the issues related to pregnancies outside of wedlock. Policy recommendations include increasing parental involvement and improving economic support to reduce the incidence of MBA marriages.